European public health policy - a common agenda to strengthen the social pillar of the EU - Hammermeister, Julia (2022)
The European Union's policy competences are divided into three different categories: exclusive, shared and supporting. The European Union has merely shared competences in regard to health policy - still it manages to affect change. This paper will examine the extent of the European health policy in regards to strengthening the European social policy.